Gubbi Theater Company _The Oldest Drama Company of Karnataka - (:unkn) unknown (My University, 2023)
The Gubbi company is the most important of the professional troops of Karnataka. It was established in 1884 and was the only professional company that delighted spectators all over India, particularly in Karnataka, for over a hundred and ten years. This company staged more than fifty plays and gave the Kannada professional theatre a new dimension. The company had its distinctive style of presenting mythological, historical, or social plays dealing with contemporary issues. Gubbi Chandana was the founder of this company. He was born in the village ‘Gulaganjihalli’, near Gubbi in the Tumkur district of Karnataka, in 1891. He had a frightening commitment to the theatre. An incident to substantiate this is when his second wife Sundaramma, who was also an artist with the company, died on the stage while enacting a play. It is said that Gubbi Chandana, who was also acting in the play along with his children, did not stop the play but allowed it to continue till the end. After the play stopped, he and his children only attended to her dead body. The Gubbi theatre company is the first theatre company in Karnataka to employ female artists to portray female characters on the stage. Elephants and horses were also brought on stage in war scenes of Kurukshetra. There is a famous saying that the story of Gubbi Veerana’s Company is the story of the Kannada theatre. The company had a troupe of more than 150 artists and backstage workers. Some famous plays staged by the company included Sadaarame and Yechamma Nayaka. These plays consisted of innovations like trick scenes, floods, clouds and rain. In those days, dramas were staged for free, with people only paying according to their liking at the end of the drama. However, Gubbi Veeranna’s dramas were an exception, with people willing to buy tickets to watch them. Most of the actors and actresses that entered the Kannada cinema world in those days were from his drama company. Later the company opened branches in different places. An important branch of the company was the Mysore branch which staged famous plays, and the finances generated from this branch sustained the whole company. The humorist ‘Hirannaiah’ was one of the persons responsible for the popularity of the Mysore branch. The company celebrated its diamond jubilee in 1944. The achievements of the Gubbi company over hundred and ten years in stage music, stage equipment, costumes, make-up, lighting designs, stage techniques and acting formed an enduring treasure for Kannada theatre.
Keywords: Gubbi Theatre Company; Gubbi Village; Veeranna Prashasthi; Tumkur; Kumara Rama; G H Veeranna (Gubbi Veeranna); Nataka Ratna; Padmashree awardee; Gubbi; Kannada